Inhibition of LPS-stimulated ecto-adenosine deaminase attenuates endothelial cell activation. (March 2019) - Kutryb-Zajac, Barbara; Mierzejewska, Paulina; Sucajtys-Szulc, Elzbieta; Bulinska, Alicja; Zabielska, Magdalena A.; Jablonska, Patrycja; Serocki, Marcin; Koszalka, Patrycja; Milczarek, Ryszard; Jasztal, Agnieszka; Bartoszewski, Rafal; Chlopicki, Stefan; et al.
Abstract: Vascular inflammation is an important factor in the pathophysiology of cardiovascular diseases, such as atherosclerosis. Changes in the extracellular nucleotide and in particular adenosine catabolism may alter a chronic inflammation and endothelial activation. This study aimed to evaluate the relation between vascular ecto-adenosine deaminase (eADA) activity and endothelial activation in humans and to analyze the effects of LPS-mediated inflammation on this activity as well as mechanisms of its increase. Moreover, we investigated a therapeutic potential of ADA inhibition by deoxycofromycin (dCF) for endothelial activation. We demonstrated a positive correlation of vascular eADA activity and ADA1 mRNA expression with endothelial activation parameters in humans with atherosclerosis. The activation of vascular eADA was also observed under LPS stimulation in vivo along with endothelial activation, an increase in markers of inflammation and alterations in the lipid profile of a rat model. Ex vivo and in vitro studies on human specimen demonstrated that at an early stage of vascular pathology, eADA activity originated from activated endothelial cells, while at later stages also from an inflammatory infiltrate. We proposed that LPS-stimulated increase in endothelial adenosine deaminase activity could be a result of IL-6/JAK/STAT pathway activation, since the lack of IL-6 in mice was associated with lower vascular and plasma eADA activities. Furthermore, the inhibitors of JAK/STAT pathway decreased LPS-stimulated adenosine deaminase activity in endothelial cells. We demonstrated that cell surface eADA activity could be additionally regulated by transcytosis pathways, as exocytosis inhibitors including lipid raft inhibitor, methyl-β-cyclodextrin decreased LPS-induced eADA activity. This suggests that cholesterol-dependent protein externalization mediated by lipid rafts could be an important factor in the eADA increase. Moreover, endocytosis inhibitors and exocytosis activators increased this activity on the cell surface. Furthermore, the inhibition of adenosine deaminase in endothelial cells in vitro attenuated LPS-mediated IL-6 release and soluble ICAM-1 and VCAM-1 concentration in the incubation medium through the restoration of the extracellular adenosine pool and adenosine receptor-dependent pathways. This study demonstrated that the vascular endothelial eADA activity remains under control of inflammatory mediators acting through JAK/STAT pathway that could be further modified by dyslipidemic-dependent exocytosis and transcytosis pathways. Inhibition of eADA blocked endothelial activation suggesting a crucial role of this enzyme in the control of vascular inflammation. This supports the concept of eADA targeted vascular protection therapy.